2010
DOI: 10.1590/s0100-69162010000500012
|View full text |Cite
|
Sign up to set email alerts
|

Potencial de erosão da bacia do Rio Uberaba

Abstract: RESUMO:Este trabalho teve por objetivo identificar qualitativamente as áreas suscetíveis à erosão laminar na bacia do Rio Uberaba, localizada em Uberaba -MG, apoiado no modelo matemático da Equação Universal de Perda de Solo (EUPS). Foram utilizadas cartas de: solos, uso e ocupação das terras, redes de drenagem, declividade e dados pluviográficos, utilizando-se de um Sistema de Informação Geográfica (SIG -IDRISI). A espacialização do potencial de erosão só foi possível a partir da estimativa da tolerância às p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 3 publications
(5 reference statements)
1
3
0
1
Order By: Relevance
“…The calculus of soil losses and tolerances in the Uberaba River basin has been presented in a previous study conducted by Valle Junior et al (2010a). The results are reproduced here for the sake of supporting a forthcoming discussion on environmental damage and consequent application of the polluter pays principle, because there are strong evidences related to human-related acceleration of soil erosion in this basin.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…The calculus of soil losses and tolerances in the Uberaba River basin has been presented in a previous study conducted by Valle Junior et al (2010a). The results are reproduced here for the sake of supporting a forthcoming discussion on environmental damage and consequent application of the polluter pays principle, because there are strong evidences related to human-related acceleration of soil erosion in this basin.…”
Section: Resultssupporting
confidence: 53%
“…This algorithm has been used in numerous studies worldwide (e.g. Martín-Fernández and Martínez-Núñez, 2011;Valle Junior et al, 2010a), representing about one third of soil erosion assessments in Brazil (Barretto et al, 2009). Apart from conventional estimations of soil losses, the USLE has recently been used to investigate potential amplification of these losses resulting from the so-called environmental land use conflicts (Pacheco et al, 2014;Valle Junior et al, 2014a), which mean uses not conforming to land capability (the soil's natural use).…”
Section: Introductionmentioning
confidence: 99%
“…Results such as those obtained by several authors in different Brazilian watersheds, under different conditions, showed mean values varying from 2.0 to 50 t.ha -1 .year -1 (AVANZI et al, 2013;SILVA et al, 2008;SILVA et al, 2011;VALLE JUNIOR et al, 2010;TEN CATEN;MINELLA;MADRUGA, 2012). However, in most cases, the method used in the simulation was MUSLE.…”
Section: Resultsmentioning
confidence: 79%
“…Considering all the factors discussed above, the Uberaba River contains a diverse and heterogeneous fish fauna, with two endemic species, H. uberaba and an undescribed crenuchid (a description is in the process by Ribeiro et al) and a low number of allochthonous and exotic species. The Uberaba River has undergone several anthropogenic actions over the last decades, such as the increase of the area destined to grazing, resulting in only 17.7% of native vegetation remains (Valle-Junior et al 2010) and the reduction of the lotic environments due to damming. The impact of human-induced environmental change is dramatic on the structure and composition of the local fauna.…”
Section: Discussionmentioning
confidence: 99%